Clinical study of carcinoma breast - H., Suresh Clement; Babu, S. Madhu; Ahmad, Samir; M., Harsha Omkar (International Surgery Journal, 2017)
Background: Inner lining of lobules or ducts of milk of breast tissue is the origin of the breast cancer. Among females, it constitutes 10.4% of cancer cases incidence all over the world. It thus is the fifth leading cause of mortality all over the world. As known, it is more common in females than males. The objective of this study was to study the clinical and epidemiological profile of breast cancer patients. Methods: A hospital based cross sectional study was carried out for a period of two and half years at M. G. M. Hospital, Warangal. Both males and females of 30 years and above were included in the study. Total number of carcinoma cases admitted during 2005 to 2007 for a period of two and half years were 1,428. Total number of carcinoma breast cases admitted during 2005 to 2007 for a period of two and half years were 242. Results: Maximum cases i.e. 44.6% belonged to stage III of breast cancer. Maximum cases were seen among Hindus i.e. 76.4%. As expected, only one case was reported by males which constituted only 0.42%. Highest number of cases i.e. 99 (40.9%) were reported during the age group of 40-50 years. Multi para women constituted more number of cases in 78.8%. Maximum number of cases of breast cancer i.e. 41.6% occurred among menstruating women. Most commonly affected quadrant was upper outer in 55.1% of cases. The most common type was Schirrous carcinoma in 39.6% of cases. Conclusions: Upper outer quadrant was most commonly affected. This indicates that the women in the reproductive age group should be directed to examine their breast daily with specific attention to upper outer quadrant.